2017
DOI: 10.21595/jve.2017.18750
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical investigation and experimental test on aerodynamic noises of the bionic rear view mirror in vehicles

Abstract: At present, there are some researches focusing on optimization of aerodynamic noises on rear view mirrors, but researches on bionic noise reduction of rear view mirrors are rarely reported. Therefore, with an original rear view mirror as the basic model, the paper applied a head convex hull of a dung beetle to the original rear view mirror cover to obtain a bionic rear view mirror, then conducted numerical computation for aerodynamic noises of the bionic rear view mirror and compared the computational results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Based on these drag-reduction theories, many researchers investigated non-smooth groove surfaces. Table 4 presents the current status of domestic and overseas research into trench drag-reduction [103,[110][111][112][113][114][115][116][117][118][119][120][121][122]. V-shaped groove shows the best drag reduction effect.…”
Section: Simulation and Experimental Study Of Bionic Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Based on these drag-reduction theories, many researchers investigated non-smooth groove surfaces. Table 4 presents the current status of domestic and overseas research into trench drag-reduction [103,[110][111][112][113][114][115][116][117][118][119][120][121][122]. V-shaped groove shows the best drag reduction effect.…”
Section: Simulation and Experimental Study Of Bionic Microstructurementioning
confidence: 99%
“…Deduces the geometry of the vortex street traveling wave. [121] Lateral groove Simulation Different groove size. When the height and width are the same, it shows the best drag reduction effect.…”
Section: Experiments and Simulationmentioning
confidence: 99%
“…The result showed that inappropriate geometrical design features of sideview mirrors could significantly exacerbate the flow-induced vibration levels of the mirror assembly. Wan and Ma (2017) applied the convex body structure of the dung beetle head to the original side-view mirror cover to reduce aerodynamic noise. The study showed that the improved side-view mirror could achieve a maximum noise reduction of 10 dB in the midhigh frequency region.…”
Section: Introductionmentioning
confidence: 99%
“…Although the side mirrors are small, it still has a drag coefficient when driving at high speeds. The drag caused by the side-view mirrors generally accounts for 2-5% of the overall drag of the vehicle (Wan and Ma 2017). To reduce this drag force, the airflow over the side-view mirror needs to be low turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…To measure noise sources, wind tunnel testing is still a common method in the automotive industry [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%